The impact of organic bananas in Alto Beni, Bolivia - Garming, H.; Gotor, Elisabetta; Cherfas, J. (2012)
This Impact Brief reports on an assessment using an asset-based livelihoods approach and carried out in 2009, five years after the end of the project. Overall, about 85% of farm families in the region said their incomes had increased since the end of the project, and the community enterprise grew in terms of both sales and membership. The project clearly initiated and catalyzed the developments that resulted in these outcomes. The impact assessment also identified elements that could be used to strengthen any future similar projects; a greater ongoing investment in the community enterprise, particularly in social and human capital, and decentralization to meet farmers’ preferred methods of working are two examples.